Connection Input Mapping and 3D Reconstruction of the Brainstem and Spinal Cord Projections to the CSF-Contacting Nucleus - Song, Si-Yuan; Li, Ying; Zhai, Xiao-Meng; Li, Yue-Hao; Bao, Cheng-Yi; Shan, Cheng-Jing; Hong, Jia; Cao, Jun-Li; Zhang, Li-Cai (Frontiers in Neural Circuits, 2020)
Objective To investigate whether the CSF-contacting nucleus receives brainstem and spinal cord projections and to understand the functional significance of these connections. Methods The retrograde tracer cholera toxin B subunit (CB) was injected into the CSF-contacting nucleus in Sprague-Dawley rats according the previously reported stereotaxic coordinates. After 7-10 days, these rats were perfused and their brainstem and spinal cord were sliced (thickness, 40 μm) using a freezing microtome. All the sections were subjected to CB immunofluorescence staining. The distribution of CB-positive neuron in different brainstem and spinal cord areas was observed under fluorescence microscope. Results The retrograde labelled CB-positive neurons were found in the midbrain, pons, medulla oblongata, and spinal cord. Four functional areas including one hundred and twelve sub-regions have projections to the CSF-contacting nucleus. However, the density of CB-positive neuron distribution ranged from sparse to dense. Conclusion Based on the connectivity patterns of the CSF-contacting nucleus receives anatomical inputs from the brainstem and spinal cord, we preliminarily conclude and summarize that the CSF-contacting nucleus participates in pain, visceral activity, sleep and arousal, emotion and drug addiction. The present study firstly illustrates the broad projections of the CSF-contacting nucleus from the brainstem and spinal cord, which implies the complicated functions of the nucleus especially for the unique roles of coordination in neural and body fluids regulation.